Book Reviews (Blackfriars, 1930)
Book reviewed in this article: The Life of Bishop Hedley By J. Anselm Wilson, D.D., Monk of Ampleforth Abbey. Horæ Diurnæ Breviarii Romani. Pii Papæ x auctoritate reformati: 6¼× 4 inches. History of the Papacy in the Nineteeth Century (1864–1878). By the late. J. B. Bury, Regus Professor of Modern History; edited with a Memoir by the Rev. R. H. Murray, Litt.D. L'Amour de Dieu et la Croix de Jesus. By P. Reg. Garrigou-Lagrange, O.P. Gerard Manley Hopkins. By G. F. Lahey, S.J. The Theology of the New Testament. By Fr. Lemonnyer, O.P. Translated by the Rev. W. A. Spence, M.A. Some Notes on the Petrine Claims. By Friedric von Hügel. The School by the River. By Elinor M. Brent-Dyer. God and Man. By the late Dean Rashdall. An Introduction to Philosophy. By Jacques Maritain. Translated by E. I. Watkin. A Treatise of the Canon of Medicine of Avicenna. By O. CAmeron Gruer, M.D., Lond. The Tragedy of the Stuarts. By J. Desmond Gleeson. The Kingdom of God in the Soul. By Father John Evangelist of Bois-le-duc (Balduke). Vernon Johnson: One Lord: One Faith. Father Vernon and His Critics. By G. J. MacGillivray, M.A., Fisher House, Cambridge. The Pocket Missal. Compiled by Father Aloysius, O.S.F.C. Lourdes. By Aileen Mary Clegg.